When grand ambitions meet the harsh realities of filmmaking: Celebrating the 100th anniversary of two classic letters by Danish director Carl Th. Dreyer on his artistically ambitious silent film Leaves from Satan's Book. Issue 2 (1st June 2019) - Thorsen, Isak; Redvall, Eva Novrup
The short subject is devoted to two letters from Carl Th. Dreyer to the management of the film company Nordisk Films Kompagni, written in 1919 just before Dreyer commenced the production of Blade af Satans Bog (Leaves from Satan's Book). The letters offer an insight into the conflict between Dreyer's artistic ambitions and financial realities.